Edukasi Berbagai Alternatif Sumber Pendanaan Bagi Pengembangan UMKM - I Gst Kt A Andri Kurniaditama; Muhammad Chayyan Bagaskara; Trisna Aditya; Luh Putu Mahyuni (Universitas Lancang Kuning, 2022)
The purpose of this community outreach program is to introduce and educate the MSMEs community that they can access various funding sources to support their business, such as banks, cooperatives, Village Credit Institution (LPD), Village-owned Enterprises (BUMDes), and Financial Technology. These funding sources can be accessed to help MSMEs develop their businesses both in terms of quantity and quality. This program, was carried out in three different places, namely Tabanan Regency, Denpasar and Jembrana Regency. The community outreach program begins with observations and interviews with MSMEs actors and provides several questions related to capital and capital institutions related to MSMEs. The next stage is the online education stage between MSME actors as online participants and community service participants as material providers. The last stage is a survey again with questions given at the beginning to find out whether the education stage provides more understanding to MSMEs actors or not. The results of this study are that MSMEs actors are more educated and understand that there are several alternatives that can be chosen to help with their capital. MSMEs actors just need to be more careful and selective so they can get a safe source of funding.